RELATIONSHIP OF TEACHING SKILLS WITH STUDENT LEARNING OUTCOMES IN THE FIELD OF ISLAMIC RELIGIOUS ECUDATION AND MORAL STUDIES AT SMPN 2 TOMPOBULU, GOWA REGENCY (International Conference on Social and Islamic Studies, 2022)
This thesis examines the "Relationship of Teaching Skills with Student Learning Outcomes in the Field of Islamic Religious Education and Moral Studies at SMPN 2 Tompobulu, Gowa Regency" which aims to: 1) Describe the teaching skills of educators in the field of Islamic religious education and Moral Education at SMPN 2 Tompobulu Gowa Regency; 2) Describe the learning outcomes of students in the field of study of Islamic religious education and morals at SMPN 2 Tompobulu, Gowa Regency; 3) Describe the relationship between the teaching skills of educators and student learning outcomes in the field of study of Islamic religious education and morals at SMPN 2 Tompobulu, Gowa Regency. This research is an ex-post-facto quantitative research which consists of two variables, namely the teacher's teaching skills variable (X) and student learning outcomes variable (Y). The population in this study were all 129 students of SMPN 2 Tompobulu, Gowa Regency, while the sample was students of class VIIIA and class VIIIB, totaling 44 people. The instruments used in data collection were questionnaires used to obtain data on teaching skills of educators and documentation used to obtain data on student learning outcomes. The data analysis technique used in this study is descriptive analysis to answer the first and second problem formulations, then inferential analysis using the correlation product moment formula to find the relationship between variables X and Y. Through these two data analysis techniques, the results of the study show that there is a relationship between the teaching skills of educators and student learning outcomes in the field of study of Islamic religious education at SMPN 2 Tompobulu, Gowa Regency where rcount = 0.995 > rtable = 0.304. The implications of this research are 1) Educators as subjects in education especially in learning should be able to understand, master and apply teaching skills properly in the learning process so that effective and efficient learning objectives can be achieved. 2) For students at SMPN 2 Tompobulu, Gowa Regency, to be able to understand their abilities and potential so that they can develop quickly in order to increase learning outcomes. 3) Principals of SMPN 2 Tompobulu, Gowa district, should always pay more attention to educators whose teaching skills are not optimal, especially educators in the field of study of Islamic religious education.